The mechanical behaviors of corrugated sandwich panel under quasi-static and dynamic shear-compressive loadings. (October 2021) - Hou, B.; Wang, Y.; Tang, Z.B.; Zhao, H.; Xi, X.L.; Li, Y.L.
Highlights: New Rotatable Hopkinson Bar is used for dynamic shear-compression on corrugated sandwich panel. Three deformation modes of corrugations are identified for different loading conditions. Loading rate effect under various combined loading is examined and attributed to inertia effect. Abstract: This paper studies the quasi-static and dynamic mechanical behaviors of a commercial corrugated sandwich panel under combined shear-compressive loading by using a modified MTS machine and the so-called Rotatable Hopkinson Bar (RHB) loading system. Particular focus is placed on identifying the differences of large deformation behaviors of corrugation panels between uniaxial compression and combined shear-compression, especially the influences of shear-compressive loading angle and loading rate on the stress-displacement curves and the deformation modes. It is found that the normal stress decreases with the loading angle, while the shear stress increases with it for both the quasi-static and dynamic loadings. Three deformation patterns are identified for five different loading angles from 0 o (corresponding to uniaxial compression) to 50 o . A positive loading rate effect is found for the initial collapse of corrugated panels, which is contributed to the inertia effect within corrugation buckling. The strength of the panels after initial collapse shows a negative loading rate effect, which may be due to the strain softening behavior of base material (5754-H48 Aluminum alloy) at impact loading.